Partial Weight-Bearing in Female Rats: Proof of Concept in a Martian-Gravity Analog - Semple, Carson; Riveros, Daniela; Nagy, Janice A.; Rutkove, Seward B.; Mortreux, Marie (Frontiers in Physiology, 2020)
Many studies have investigated the physiological response to microgravity in both astronauts and animals. However, while space agencies have sought to deploy more women on their missions; animal models rarely include females studies or comparisons between males and females. Therefore, we exposed adult female rats to two weeks of partial weight-bearing at either 100% of their normal loading (PWB100) or 40% of their normal loading (PWB40), corresponding to Martian gravity-analog, and assess muscle function, force and histomorphometry. Females exposed to PWB showed an 11.62% decline in hindlimb grip force associated with an 11.84% decrease in soleus myofiber size after 14 days of exposure, while maintaining normal blood oxygenation and stress levels. This pilot study represents the first experiment designed to understand the muscular disuse associated with a partial reduction in mechanical loading in female rats, and the first step needed to develop successful mitigating strategies.